Evaluation of various antibiotics on growth rate and feed efficiency of finishing pigs - Allee, G.L.; Noll, M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used 150 Yorkshire finishing pigs averaging 120 lbs initially to evaluate the following antibotics: Tylan, Stafac, Oleandomycin, and Flavomycin on rate and efficiency of gain. The trial ended when pigs within a replicate averaged approximately 220 lbs. There were no significant differences in rate or efficiency of gain by pigs fed nonmedicated or medicated diets.
Keywords: Swine; Antibiotics; Growth rate; Feed Efficiency; Finishing pigs